2016
DOI: 10.1155/2016/5162167
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hypogonadism in Male Patients with Type 2 Diabetes

Abstract: Background. Male hypogonadism is an endocrine disease characterized by low levels of serum testosterone and is closely related to the development of diabetes. The purpose of the present study was to observe the risk factors for hypogonadism in male patients with type 2 diabetes. Methods. A total of 213 patients with type 2 diabetes were enrolled and divided into a low total testosterone (TT) group (=75) and a normal TT group (=138). The patients' blood glucose, blood lipids, serum insulin, and sex hormones wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 38 publications
(37 reference statements)
6
23
1
2
Order By: Relevance
“…Some studies reported decline with age while other deny this association. 8,17,32 A longer duration of DM not correlated with TT levels nor MHG prevalence as this result is inconsistent with other research. 8 while in agreement with other studies.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Some studies reported decline with age while other deny this association. 8,17,32 A longer duration of DM not correlated with TT levels nor MHG prevalence as this result is inconsistent with other research. 8 while in agreement with other studies.…”
Section: Discussioncontrasting
confidence: 90%
“…17,34,35 In contrast, other studies correlated lower HDL-c and higher triglyceride levels were significantly with LST in T2DMs. 9,36 In the present study, smoker ratio was significantly higher in MHG patient but regression analysis showed no significant correlation between smoking and MHG, The relation of smoking with testosterone was controversial, some studies had shown a positive association between smoking and total or FT levels, also smoking cessation decreased testosterone levels in men followed for idiopathic infertility, while some studies found no association.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies have indicated that male hypogonadism is caused by a variety of chronic diseases, such as type 2 diabetes, and it is characterized by low levels of total testosterone and an increase in gonadotropins. These changes are related to a steroidogenesis defect in Leydig cells, as shown by both in vivo and in vitro studies [34]. Sexual organ disorders in diabetic cases can also result from oxidative stress and the imbalance between reactive oxygen species (ROS) generation and antioxidant enzyme activity [5].…”
Section: Introductionmentioning
confidence: 99%